2018
DOI: 10.3389/fphar.2018.01407
|View full text |Cite
|
Sign up to set email alerts
|

The South African Regulatory System: Past, Present, and Future

Abstract: The drive for improved regulatory systems and the establishment of a more effective regulatory framework in South Africa has been evident for the past two decades but despite political intentions and legislative revisions success has been limited to date. Efforts to address the increasing volume of applications that have been received have to date failed and resources have been stretched to capacity resulting in the development of a significant backlog and extended timelines for product registration. The promu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…As such, it is critical to any improvement to ensure the routine and accurate measurement and monitoring of performance metrics of the regulatory review process. Benchmarking milestones currently used by NRAs typically include the times for receipt and validation, scientific assessment, applicants' response, and market authorization to be granted as well as the time taken to complete all administrative activities [9]. The data collected from the MCC and SAHPRA for the period 2015-2018 demonstrated that several of these milestones were recorded, but not measured and monitored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, it is critical to any improvement to ensure the routine and accurate measurement and monitoring of performance metrics of the regulatory review process. Benchmarking milestones currently used by NRAs typically include the times for receipt and validation, scientific assessment, applicants' response, and market authorization to be granted as well as the time taken to complete all administrative activities [9]. The data collected from the MCC and SAHPRA for the period 2015-2018 demonstrated that several of these milestones were recorded, but not measured and monitored.…”
Section: Discussionmentioning
confidence: 99%
“…The overall approval timelines for the regulatory review achieved by the MCC (2015-2017) and by SAHPRA (2018) are extensive and do not contribute to ensuring timely access to medicines for patients in South Africa. Keyter et al previously described both the historical and operational factors that have contributed to these extended timelines [9]. While there are currently no comparative studies available to reflect the regulatory performance of South Africa relative to other African countries, it has been noted that a target overall approval timeline of 330 calendar days has been set by the Zazibona collaborative process [10], a harmonization and joint-review initiative in the Southern African Development Community (SADC) region, in which South Africa has participated since 2016.…”
Section: Regulatory Review Approval Timelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor hiring policies limit performance; for example, NRAs commonly hire pharmacists in roles requiring different competencies than what they were trained for. NRAs disproportionally allocate resources on upstream functions (Figure 1) that can be simplified or de-duplicated through regulatory harmonization (36). Finite NRA resources should instead be spent on downstream functions such as post-market surveillance and detection of illegitimate drugs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…South Africa also has the strongest pharmaceutical sector amongst sub-Saharan African countries (15). A recent change in the pharmaceutical regulatory authority, from the Medicines Control Council to the South African Health Products Regulatory Authority, created backlogs and uncertainty while the new regulatory agency was in the set-up phase (16). This combination of high medical expenditure and potentially still weak pharmaceutical regulatory capacity given the transition to a new regulatory authority provides the potential for SF products to spread.…”
Section: Introductionmentioning
confidence: 99%